Silicon carbide nanofiber aerogel and preparation method thereof
In the traditional silicon carbide aerogel preparation method, aramid nanofibers and SiO2 sol form an interpenetrating network structure, and are reduced by high-temperature carbon-heat, the problems of low specific surface area and large brittleness of traditional silicon carbide aerogel are solved, and its thermal insulation and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202411835095.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The silicon carbide aerogel prepared by traditional methods has low specific surface area, poor thermal insulation performance, large brittleness and fragility, which seriously affects its application.
Available aerogel with a uniform interpenetrating network nanostructures is used to form a uniform interpenetrating network nanostructures in situ, and then reduced by high-temperature carbon heat to obtain silicon carbide nanofiber aerogel.
The specific surface area and flexibility of silicon carbide aerogel are significantly improved, greatly improving its thermal insulation and mechanical properties.
Smart Images

Figure BDA0005186478370000051 
Figure BDA0005186478370000061
Abstract
Description
Technical Field
[0001] The invention relates to a silicon carbide nanofiber aerogel and a preparation method thereof, belonging to the technical field of aerogel materials. Background Art
[0002] Since the temperature resistance of silicon oxide aerogel is generally below 1000℃, carbon aerogel is easily oxidized and ineffective when used at >400℃ in air atmosphere, and organic aerogel is generally used for thermal insulation at lower temperatures, in contrast, only ceramic aerogel has excellent high temperature resistance, oxidation resistance and thermal shock resistance, and can be used for high temperature insulation above 1000℃. Silicon carbide (SiC) aerogel, as a typical ceramic aerogel, has excellent properties such as wide energy band gap, high temperature stability, low thermal expansion coefficient, high mechanical strength, good thermal shock resistance, oxidation resistance and corrosion resistance, and is particularly suitable for a variety of applications in high temperature and highly corrosive environments, such as high temperature insulation, electromagnetic wave absorption, filtration and catalyst carriers.
[0003] Using organic / SiO2 composite aerogel as a precursor and high-temperature carbon thermal reduction under an inert atmosphere is a common method for preparing SiC aerogel. Using commonly used organic precursors, such as polyacrylonitrile and phenolic aldehyde, the prepared SiC aerogel has a low specific surface area (generally not more than 251m 2 / g), poor thermal insulation performance, high brittleness and easy breakage, which seriously affect the application of SiC aerogel. Therefore, how to increase the specific surface area of SiC aerogel and improve its brittleness is a technical difficulty that must be solved to realize the application of SiC aerogel. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of low specific surface area, poor thermal insulation performance, high brittleness and easy breakage of silicon carbide aerogel prepared by traditional methods, and to provide a silicon carbide nanofiber aerogel and a preparation method thereof, which significantly improves the thermal insulation performance and mechanical properties of silicon carbide aerogel by increasing the specific surface area and improving flexibility.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing silicon carbide nanofiber aerogel comprises the following steps:
[0007] 1) adding aramid fiber, deionized water and potassium hydroxide (KOH) into dimethyl sulfoxide (DMSO) under high-speed mechanical stirring to fully nano-size the aramid fiber to obtain an aramid nanofiber dispersion;
[0008] 2) Adding catalyst ammonia water to ethanol silica sol or aqueous silica sol, mixing evenly to obtain SiO2 sol containing catalyst, and storing it in a sealed state at low temperature;
[0009] 3) pouring the aramid nanofiber dispersion into a mold, and then pouring the SiO2 sol containing the catalyst onto the top of the aramid nanofiber dispersion, after the SiO2 sol is fully diffused, restoring the wet gel to room temperature, allowing the SiO2 sol to gel, and aging at room temperature to obtain an aramid nanofiber / SiO2 composite wet gel with an interpenetrating network structure;
[0010] 4) subjecting the aramid nanofiber / SiO2 composite wet gel to solvent replacement and supercritical drying to obtain the aramid nanofiber / SiO2 composite aerogel;
[0011] 5) Under the protection of inert gas, the aramid nanofiber / SiO2 composite aerogel is subjected to high-temperature carbon thermal reduction treatment in an atmosphere furnace to obtain silicon carbide nanofiber aerogel.
[0012] Furthermore, in step 1), the aramid fiber is any one or more of all-para-aramid fiber, all-para-aramid copolymer fiber, all-meta-aramid fiber, meta-aramid copolymer fiber containing methyl substituents, etc.
[0013] Furthermore, in step 1), the mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is (4-8):(4-8):(1.2-2.4):(92-84).
[0014] Furthermore, in step 1), the time for nano-forming the aramid fiber is 5 to 8 hours.
[0015] Furthermore, steps 1) and 2) are carried out at a low temperature of 5 to 10°C.
[0016] Furthermore, in step 2), the solid content of the ethanol silica sol or the aqueous silica sol is 1.18% to 5.86%, and the mass ratio of SiO2 to ammonia water in the ethanol silica sol or the aqueous silica sol is 1:(0.01 to 0.03).
[0017] Furthermore, in step 3), the mass ratio of the aramid nanofiber dispersion to the ethanol silica sol or aqueous silica sol is 2 to 4; the low-temperature diffusion time of the SiO2 sol and the aramid nanofiber dispersion is 24 to 72 hours; and the room temperature aging time of the aramid nanofiber / SiO2 composite wet gel is 24 to 48 hours.
[0018] Furthermore, in step 3), the mass ratio of aramid nanofibers to SiO2 in the aramid nanofiber / SiO2 composite wet gel is 1:(0.10-0.15).
[0019] Furthermore, in step 4), solvent replacement and supercritical drying are well-known techniques in the art. The solvent may be commonly used ethanol or acetone, etc. Those skilled in the art select the solvent and process according to the specific circumstances.
[0020] Furthermore, the step temperature increase program of the high temperature carbon thermal reduction treatment in step 5) is as follows: 1°C / min, heating to 1000°C, keeping warm for 1 to 3 hours; 1°C / min, heating to 1400 to 1500°C, keeping warm for 3 to 5 hours.
[0021] A silicon carbide nanofiber aerogel is prepared by the above preparation method.
[0022] The beneficial effects of the present invention compared with the prior art are as follows:
[0023] (1) The preparation method of the present invention uses aramid nanofibers and SiO2 sol to form an aerogel with a uniform interpenetrating network nanostructure in situ, and then undergoes high-temperature carbon thermal reduction to obtain silicon carbide nanofiber aerogel. The present invention uses aramid nanofibers as organic precursors. Compared with the commonly used organic precursors in the prior art (such as polyacrylonitrile, phenolic acid, etc.), aramid nanofibers have a higher specific surface area and good flexibility. The aramid nanofiber / SiO2 composite aerogel prepared therefrom, after high-temperature carbon thermal reduction, uses aramid nanofibers as a template to form silicon carbide nanofiber aerogel in situ, which has extremely high specific surface area and flexibility, and greatly improves the thermal insulation and mechanical properties of silicon carbide aerogel.
[0024] (2) The present invention uses aramid nanofibers as a carbon source and SiO2 sol nanoparticles as a silicon source for preparing silicon carbide nanofiber aerogel, both of which are nanometer-sized, forming a nanometer-sized composite aramid nanofiber / SiO2 composite aerogel, thereby ensuring the uniformity of the interior of the silicon carbide nanofiber aerogel after high-temperature carbon thermal reduction.
[0025] (3) The mass ratio of aramid fiber, deionized water, KOH and DMSO should be appropriate. If the ratio of aramid fiber is too low, the strength of the prepared silicon carbide nanofiber aerogel will be too poor; if the ratio of aramid fiber is too high, the aramid fiber will be difficult to fully nano-scale. If the ratio of potassium hydroxide is too low, it will be difficult to fully destroy the hydrogen bonds inside the aramid fiber, resulting in difficulty in fully nano-scale the aramid fiber; if the ratio of potassium hydroxide is too high, the aramid molecular structure will be destroyed in large quantities, resulting in the aramid nanofiber being too short, making the strength of the silicon carbide nanofiber aerogel poor.
[0026] (4) The mass ratio of aramid nanofibers to SiO2 should be appropriate. If the mass ratio of aramid nanofibers to SiO2 is too low, the residual SiO2 in the silicon carbide nanofiber aerogel will reduce the temperature resistance of the silicon carbide nanofiber aerogel. If the mass ratio of aramid nanofibers to SiO2 is too high, the residual C element will reduce the antioxidant properties of the silicon carbide nanofiber aerogel.
[0027] (5) The mass ratio of the aramid nanofiber dispersion to the ethanol silica sol or the aqueous silica sol is 2 to 4. If the mass ratio of the aramid nanofiber dispersion to the ethanol silica sol or the aqueous silica sol is too high, the aramid nanofiber dispersion gel will be too weak and will not be able to maintain a good nanopore structure during the subsequent supercritical drying process. If the mass ratio of the aramid nanofiber dispersion to the ethanol silica sol or the aqueous silica sol is too low, the concentration of the ethanol silica sol or the aqueous silica sol in the pores of the aramid nanofiber gel will be low, resulting in the silica gel being too weak and not being able to maintain a good nanopore structure during the subsequent supercritical drying process.
[0028] (6) Since the protonic solvent (ethanol or water) in the SiO2 sol is the gelling agent of the aramid nanofiber dispersion, a gel film will be formed between the two liquids. Along with the solvent exchange between the SiO2 sol and the aramid nanofiber dispersion, the aramid nanofiber dispersion will form a physical gel, and the SiO2 sol will also diffuse into the gel pores of the aramid nanofiber. After the SiO2 sol is fully diffused, the wet gel is restored to room temperature to allow the SiO2 sol to gel and age, thereby obtaining an aramid nanofiber / SiO2 composite wet gel with an interpenetrating network structure.
[0029] (7) The preparation process of the present invention is simple, the raw materials are cheap and readily available, and it is suitable for industrial production.
[0030] (8) The silicon carbide nanofiber aerogel prepared by the present invention has excellent thermal insulation performance, thermal stability and flexibility, and has broad application prospects in the field of high-temperature thermal insulation materials. DETAILED DESCRIPTION
[0031] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below in conjunction with embodiments.
[0032] Example 1
[0033] This embodiment adopts the preparation method proposed in the present invention to prepare silicon carbide nanofiber aerogel, and the steps are as follows:
[0034] 1. Under high-speed mechanical stirring, 8.00g of all-para-aramid fiber, 8.00g of deionized water, and 2.40g of KOH were added to 84.00g of dimethyl sulfoxide (DMSO) for about 5 hours to fully nano-enhance the aramid fiber to obtain an aramid nanofiber dispersion; (the mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is 8:8:2.4:84)
[0035] 2. At a low temperature of 5 to 10°C, weigh 25.60g of aqueous silica sol with a solid content of 5.86%, add 0.045g of ammonia water dropwise while stirring, mix well, and store in a sealed container at 5 to 10°C; (the mass ratio of aramid nanofiber dispersion to aqueous silica sol is 4, the mass ratio of SiO2 to ammonia water in ethanol silica sol or aqueous silica sol is 1:0.03, and the mass ratio of aramid nanofiber to SiO2 in aramid nanofiber / SiO2 composite wet gel is 1:0.15)
[0036] 3. At a low temperature of 5 to 10°C, pour the aramid nanofiber dispersion prepared in step 1 into a mold, and then pour the SiO2 sol containing the catalyst prepared in step 2 onto the aramid nanofiber dispersion. Since the water in the SiO2 sol is the gelling agent of the aramid nanofiber dispersion, a gel film will be formed between the two liquids, and the SiO2 sol and the aramid nanofiber dispersion will undergo solvent exchange. After about 24 hours, the aramid nanofiber dispersion will form a physical gel, and the SiO2 sol will also diffuse into the gel pores of the aramid nanofiber. The wet gel is restored to room temperature to allow the SiO2 sol to gel, and aged at room temperature for 24 hours to obtain an aramid nanofiber / SiO2 composite wet gel with an interpenetrating network structure.
[0037] 4. The aramid nanofiber / SiO2 composite wet gel obtained in step 3 was subjected to solvent replacement, soaked in ethanol for three times, and then dried with supercritical CO2 at 40°C and 15MPa for 8h to obtain the aramid nanofiber / SiO2 composite aerogel.
[0038] 5. Under Ar gas protection, the aramid nanofiber / SiO2 composite aerogel was subjected to high-temperature carbon thermal reduction treatment in an atmosphere furnace (the step-by-step heating program is as follows: 1°C / min, heating to 1000°C, keeping warm for 2h; 1°C / min, heating to 1400°C, keeping warm for 3h) to obtain silicon carbide nanofiber aerogel.
[0039] The test results of the silicon carbide nanofiber aerogel obtained in this example are listed in Table 1.
[0040] Example 2
[0041] Except that the added aramid fiber is all-meta-aramid fiber, the preparation conditions and process of silicon carbide nanofiber aerogel are the same as those in Example 1. The test results of the performance of silicon carbide nanofiber aerogel are listed in Table 1.
[0042] Example 3
[0043] Except that the added silica sol is ethanol silica sol, the preparation conditions and process of silicon carbide nanofiber aerogel are the same as those in Example 1. The test results of the properties of silicon carbide nanofiber aerogel are listed in Table 1.
[0044] Example 4
[0045] The preparation conditions and process of silicon carbide nanofiber aerogel are the same as those in Example 1, except that the mass of aqueous silica sol is 51.2 g, the solid content thereof is 2.33%, and the mass of ammonia water is 0.0119 g. The test results of the properties of silicon carbide nanofiber aerogel are listed in Table 1. (The mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is 8:8:2.4:84; the mass ratio of aramid nanofiber dispersion to aqueous silica sol is 2, the mass ratio of SiO2 to ammonia water in aqueous silica sol is 1:0.01, and the mass ratio of aramid nanofiber to SiO2 in aramid nanofiber / SiO2 composite wet gel is 1:0.10)
[0046] Example 5
[0047] The preparation conditions and process of silicon carbide nanofiber aerogel are the same as those in Example 1, except that the mass of aqueous silica sol is 40 g, the solid content thereof is 3.34%, and the mass of ammonia water is 0.0267 g. The test results of the properties of silicon carbide nanofiber aerogel are listed in Table 1. (The mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is 8:8:2.4:84; the mass ratio of aramid nanofiber dispersion to aqueous silica sol is 2.56, the mass ratio of SiO2 to ammonia water in aqueous silica sol is 1:0.02, and the mass ratio of aramid nanofiber to SiO2 in aramid nanofiber / SiO2 composite wet gel is 1:0.12)
[0048] Example 6
[0049] Except that the addition amount of all-para-aramid fiber is 4.00g, the addition amount of deionized water is 4.00g, the addition amount of KOH is 1.20g, the addition amount of dimethyl sulfoxide (DMSO) is 92.00g, the mass of aqueous silica sol is 50.60g, the solid content thereof is 1.18%, and the addition amount of ammonia water is 0.0119g, the preparation conditions and process of silicon carbide nanofiber aerogel are the same as those in Example 1, and the test results of the performance of silicon carbide nanofiber aerogel are listed in Table 1. (The mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is 4:4:1.2:92; the mass ratio of aramid nanofiber dispersion to aqueous silica sol is 2, the mass ratio of SiO2 to ammonia water in aqueous silica sol is 1:0.02, and the mass ratio of aramid nanofiber to SiO2 in aramid nanofiber / SiO2 composite wet gel is 1:0.10)
[0050] Example 7
[0051] Except that the addition amount of all-para-aramid fiber is 6.00g, the addition amount of deionized water is 6.00g, the addition amount of KOH is 1.80g, the addition amount of dimethyl sulfoxide (DMSO) is 88.00g, the mass of aqueous silica sol is 50.90g, the solid content thereof is 1.76%, and the addition amount of ammonia water is 0.0179g, the preparation conditions and process of silicon carbide nanofiber aerogel are the same as those in Example 1, and the performance test results of silicon carbide nanofiber aerogel are listed in Table 1. (The mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is 6:6:1.8:88; the mass ratio of aramid nanofiber dispersion to aqueous silica sol is 2, the mass ratio of SiO2 to ammonia water in aqueous silica sol is 1:0.02, and the mass ratio of aramid nanofiber to SiO2 in aramid nanofiber / SiO2 composite wet gel is 1:0.10)
[0052] Comparative Example
[0053] According to the molar ratio of resorcinol, formaldehyde (37% w / w aqueous solution), 3-aminopropyl triethoxysilane, ethyl orthosilicate, anhydrous ethanol, and sodium carbonate of 1:2:0.2:0.8:60:2, mix them evenly at room temperature to obtain a mixed solution. Pour the mixed solution into a mold, seal and cure at 60°C to obtain a phenolic / SiO2 hybrid wet gel, and age at 75°C for 24h. Soak it repeatedly in ethanol for 3 times, then dry it with supercritical CO2, and dry it at 40°C and 15MPa for 8h to obtain a phenolic / SiO2 hybrid aerogel.
[0054] Under the protection of Ar gas, the phenolic / SiO2 hybrid aerogel was subjected to high-temperature carbon thermal reduction treatment in an atmosphere furnace (1°C / min, heating to 1500°C, and keeping warm for 5h) to obtain silicon carbide aerogel.
[0055] Table 1 Performance test results of silicon carbide nanofiber aerogels obtained in Examples 1 to 7 and Comparative Examples
[0056]
[0057]
[0058] As can be seen from the data in Table 1, the silicon carbide nanofiber aerogel provided by the present application has light weight, high specific surface area, low room temperature thermal conductivity, high temperature resistance and high resilience, and its performance is significantly better than that of the silicon carbide aerogel prepared in the comparative example. The present invention effectively solves the problems of low specific surface area, poor thermal insulation performance, high brittleness and easy breakage of SiC aerogel prepared by the prior art, and has broad application prospects in the field of high temperature thermal insulation materials.
[0059] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.
Claims
1. A method for preparing silicon carbide nanofiber aerogel, characterized in that: The following steps are involved: 1) adding aramid fiber, deionized water and potassium hydroxide into dimethyl sulfoxide under high-speed mechanical stirring to fully nano-size the aramid fiber to obtain an aramid nanofiber dispersion; 2) Adding catalyst ammonia water to ethanol silica sol or aqueous silica sol, mixing evenly to obtain SiO2 sol containing catalyst, and storing it in a sealed state at low temperature; 3) pouring the aramid nanofiber dispersion into a mold, and then pouring the SiO2 sol containing the catalyst onto the top of the aramid nanofiber dispersion, after the SiO2 sol is fully diffused, restoring the wet gel to room temperature, allowing the SiO2 sol to gel, and aging at room temperature to obtain an aramid nanofiber / SiO2 composite wet gel with an interpenetrating network structure; 4) subjecting the aramid nanofiber / SiO2 composite wet gel to solvent replacement and supercritical drying to obtain the aramid nanofiber / SiO2 composite aerogel; 5) Under the protection of inert gas, the aramid nanofiber / SiO2 composite aerogel is subjected to high-temperature carbon thermal reduction treatment in an atmosphere furnace to obtain silicon carbide nanofiber aerogel.
2. The preparation method according to claim 1, characterized in that In step 1), the aramid fiber is any one or more of all-para-aramid fiber, all-para-aramid copolymer fiber, all-meta-aramid fiber, meta-aramid copolymer fiber containing methyl substituents, etc.
3. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of aramid fiber, deionized water, potassium hydroxide and dimethyl sulfoxide is (4-8):(4-8):(1.2-2.4):(92-84).
4. The preparation method according to claim 1, characterized in that: In step 1), the time for nano-forming the aramid fiber is 5 to 8 hours.
5. The preparation method according to claim 1, characterized in that: Steps 1) and 2) are carried out at a low temperature of 5 to 10°C.
6. The preparation method according to claim 1, characterized in that: In step 2), the solid content of the ethanol silica sol or the aqueous silica sol is 1.18% to 5.86%, and the mass ratio of SiO2 to ammonia water in the ethanol silica sol or the aqueous silica sol is 1:(0.01 to 0.03).
7. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of aramid nanofiber dispersion to ethanol silica sol or aqueous silica sol is 2-4; the low-temperature diffusion time of SiO2 sol and aramid nanofiber dispersion is 24-72h; and the room temperature aging time of aramid nanofiber / SiO2 composite wet gel is 24-48h.
8. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of aramid nanofibers to SiO2 in the aramid nanofiber / SiO2 composite wet gel is 1:(0.10-0.15).
9. The preparation method according to claim 1, characterized in that: In step 5), the step-wise heating program of the medium- and high-temperature carbon thermal reduction treatment is as follows: 1°C / min, heating to 1000°C, keeping warm for 1 to 3 hours; 1°C / min, heating to 1400 to 1500°C, keeping warm for 3 to 5 hours.
10. A silicon carbide nanofiber aerogel, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Carbon-silicon carbide nanofiber aerogel with 3D core-shell structure and preparation method of carbon-silicon carbide nanofiber aerogel
CN121046993A